Sports coaching professionalisation and practice - Lyle, John; Cushion, Chris (Churchill Livingstone, 2010)
Sports Coaching: Professionalisation and Practice is a comprehensive evidence-based textbook of sports coaching theory and practice. The book is edited by leading academics in sports coaching studies and authored by a world-renowned team of experts in sports coaching research. It deals with all aspects of coaching behaviour and practice, including coaches' decision making, coaching pedagogy, and the development of expertise. Each of the chapters provides an up-to-date position statement on coaching themes, and makes explicit reference to the professionalisation of coaching. Written in an accessible style, and identifying critical ideas and issues, the book will complement and challenge both undergraduate and postgraduate teaching programmes, and will be an invaluable source of ideas for researchers and academics.